Steam reforming of polystyrene at a low temperature for high H2/CO gas with bimetallic Ni-Fe/ZrO2 catalyst - Zhou H.; Saad J.M.; Li Q.; Xu Y. (Elsevier Ltd, 2023)
Binary alloys; Carbon dioxide; Catalysts; Chemical shift; Deposition; Hydrogen; Iron alloys; Nickel alloys; Polystyrenes; Steam; Temperature; Water gas shift; Bimetallic catalysts; Carbon deposition; Catalyst surfaces; High temperature; Low temperatures; Temperature range; Thermodynamic equilibrium calculation; Water gas shift (WGS) reaction; Steam reforming; alloy; carbon dioxide; carbon monoxide; hydrogen; iron; nickel; polystyrene; water; zirconium oxide; nickel; polystyrene derivative; carbon dioxide; carbon emission; catalyst; hydrogen; low temperature; temperature effect; waste technology; waste treatment; Article; catalyst; chemical reaction; comparative study; controlled study; gas; gas analysis; low temperature; online analysis; priority journal; recycling; steam reforming; surface property; synthesis; water vapor; catalysis; temperature; Catalysis; Nickel; Polystyrenes; Steam; Temperature